2022
DOI: 10.3233/nre-210255
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lateral truncal tilt training with a wedge on postural vertical and activities of daily living in recovery phase after stroke: A randomized crossover trial

Abstract: BACKGROUND: The subjective postural vertical (SPV) is affected by training that requires participants to maintain balance; training to achieve sitting balance may also help SPV recovery and activities of daily living (ADLs). OBJECTIVE: This study aimed to assess the medium-term effects of balance training on the postural vertical (PV) and ADLs in patients with stroke. METHODS: Thirty-three patients with stroke were enrolled in this randomized crossover trial. The outcomes were SPV, SPV with eyes opened (SPV-EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In addition, patients with Pusher syndrome with USN have increased SPV-EO variability errors due to directional attention disorder (Sawa et al, 2022;Corbetta & Shulman, 2011;Karnath, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with Pusher syndrome with USN have increased SPV-EO variability errors due to directional attention disorder (Sawa et al, 2022;Corbetta & Shulman, 2011;Karnath, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The starting direction of the tilt measurements was left or right, based on the ABBABAAB or BAABABBA sequences. The standard deviation of eight measurements was used as the PV tilt variability (Fukata et al, 2020;Sawa et al, 2022).…”
Section: Measurement Of Subjective Postural Vertical Valuesmentioning
confidence: 99%
“…2B). [4,21] The SPV-EO and SPV measurements were performed on the left and right sides in a counterbalanced order, using ABBABAAB or BAABABBA sequences. Participants indicated when they perceived themselves as being in a true vertical position, and the tilt of the VB was recorded using a digital inclinometer.…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that sitting balance training improved variability by enhancing verticality cognition and the ability to perform activities of daily living, as supported by longitudinal studies. [4,5] However, the mechanism by which sitting balance training affects sitting pressure has not yet been clarified. On the other hand, recent reviews have revealed that various sensory and higher brain functions contribute to the vertical perception in balance components.…”
Section: Introductionmentioning
confidence: 99%
“…The starting direction of the tilt measurements was left or right, based on the ABBABAAB or BAABABBA sequences. The standard deviation of eight measurements was used as the PV tilt variability [16,20].…”
Section: Measurement Of Spvmentioning
confidence: 99%